2009
DOI: 10.1016/j.entcs.2009.02.041
|View full text |Cite
|
Sign up to set email alerts
|

The Tractability of Model-checking for LTL: The Good, the Bad, and the Ugly Fragments

Abstract: In a seminal paper from 1985, Sistla and Clarke showed that the model-checking problem for Linear Temporal Logic (LTL) is either NP-complete or PSPACE-complete, depending on the set of temporal operators used. If, in contrast, the set of propositional operators is restricted, the complexity may decrease. This paper systematically studies the model-checking problem for LTL formulae over restricted sets of propositional and temporal operators. For almost all combinations of temporal and propositional operators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…For example, we might want to stipulate the a 7 For example, suppose that there is a set Si of initial states for every system S, T designates the system's reachability or, synonymously, temporal accessibility relation, and T * designates the reflexive transitive closure of T. Then, S is induced by S in the sense that S := { s | there is si ∈ Si such that si T * s }. 8 for all s ∈ S, there is s ∈ S s.t. Doxastic accessibility D a ⊆ E a can be defined from E a by weakening the reflexivity of E a to seriality as appropriate for the considered application.…”
Section: Definition 1 (Framework) Letmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we might want to stipulate the a 7 For example, suppose that there is a set Si of initial states for every system S, T designates the system's reachability or, synonymously, temporal accessibility relation, and T * designates the reflexive transitive closure of T. Then, S is induced by S in the sense that S := { s | there is si ∈ Si such that si T * s }. 8 for all s ∈ S, there is s ∈ S s.t. Doxastic accessibility D a ⊆ E a can be defined from E a by weakening the reflexivity of E a to seriality as appropriate for the considered application.…”
Section: Definition 1 (Framework) Letmentioning
confidence: 99%
“…Table 2. Examples of agent correctness -algorithm, game-rule, and protocol compliance -good book-keeping in audit and control of transactions -fairness in the scheduling of legitimately requested services -liveness in the sense of absence of crash, e.g., that the agent, say a, has always eventually responded to a ping from some other agent, say b, which can be expressed with a Linear-Temporal Logic [28,27,70,8] formula as follows:…”
Section: Motivationmentioning
confidence: 99%
“…These results provide a (partial) account for the polytomous complexity classifications of problems parametrized by the set of available Boolean connectives: the complexity of the satisfiability problem was, for instance, shown to be NP-complete if x y can be composed from the available Boolean connectives, and solvable in logspace in all other cases [13]. Further results include a variety of problems in propositional logic [5,19], modal logics [1], temporal logics [2][3][4]16], their hybrid variants [14,15], and nonmonotonic logics [6,11,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches explore the computational properties of model checking and several algorithmic subclasses have been identified that are characterized by which (modal) operators are employed [29]. Model checking of manipulation tasks specified in the LTL-like logic QSL benefits from two characteristics:…”
Section: Reasoning With Qslmentioning
confidence: 99%